ANALISIS PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN KARAKTERISTIK GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN - Faizal Adi Nugroho; Shiddiq Nur Rahardjo (Diponegoro Journal of Accounting, 2014)
ABSTRACTThe aim of this research is to examine the effect of corporate social responsibility (CSR) and the characteristics of good corporate governance (GCG) to firm performance. Independent variables used in this research are CSR, board of directors, board of commissioners, and audit committee. While the dependent variable in this study is firm performance measured using return on equity (ROE).This research used a sample of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2012. The sampling method in this research is purposive sampling and acquired 77 companies that meet the criteria. Hypothesis testing using multiple regression analysis.The results of this research showed that the higher the level of CSR disclosure, board of directors, and audit committee of a company, the higher the firm performance. While board of commissioner has no effect on firm performance.